The Influence of Compensation and Work Environment on Employee Performance at Perum DAMRI Palembang City Branch - Ariq Abdullah; Hamid Halin; Meilin Veronica (International Journal of Marketing & Human Resource Research, 2023)
This study aims to determine the effect of compensation and work environment on employee performance at Perum Damri Palembang branch. The method in this study was associative research. The analysis in this research utilized multiple linear regression analysis. The results of this study indicate that there is an effect of compensation and work environment on employee performance at Perum Damri Palembang branch. This research is expected to provide benefits for companies to evaluate employee performance through compensation and work environment.